INFLUENCE OF FREEZING PROCESS ON ORGANOLEPTIC PARAMETERS OF PUFF PASTRY PRODUCTS - A. T. Prussakova; M. S. Voronina; N. V. Makarova (Современная наука и инновации)
The article describes the results of a study of the effect of the freezing process on the organoleptic characteristics of culinary products from puff pastry. The study was conducted in two stages. Qualitative indicators of experimental products were evaluated by the organoleptic method. The study revealed the influence of defrosting conditions on the appearance, color, taste, aroma and texture of finished products. And also the optimal conditions for defrosting products were selected to maintain the best organoleptic characteristics in the production process.